2015
DOI: 10.1089/dia.2014.0155
|View full text |Cite
|
Sign up to set email alerts
|

Internet Delivered Diabetes Self-Management Education: A Review

Abstract: Internet-delivered diabetes education has the added benefit of easier access for many individuals, and patients can self-pace themselves through materials. More research on the cost-benefits of Internet diabetes education and best methods to maintain patient engagement are needed, along with more studies assessing the long-term impact of Internet-delivered DSME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 28 publications
1
101
1
5
Order By: Relevance
“…Creative solutions incorporating technology to increase reach and engagement must be examined (73,74). Telehealth, electronic health records (EHR), mobile applications, and cognitive computing will proactively identify and track participants while offering endless opportunities for individualized and contextualized DSMES (16,(75)(76)(77)(78).…”
Section: Standard 3 Evaluation Of Population Servedmentioning
confidence: 99%
“…Creative solutions incorporating technology to increase reach and engagement must be examined (73,74). Telehealth, electronic health records (EHR), mobile applications, and cognitive computing will proactively identify and track participants while offering endless opportunities for individualized and contextualized DSMES (16,(75)(76)(77)(78).…”
Section: Standard 3 Evaluation Of Population Servedmentioning
confidence: 99%
“…8,9 Computer-based diabetes self-management interventions currently have limited effectiveness and reduce HbA 1c by about 0.2%; mobile phone users have a total reduction of 0.5%. 10,11 Perhaps the largest downside to nearly all interventions is that they measure disease-oriented, not patientoriented, evidence and then follow performance measures only for a relatively short period. Hansen et al 12 followed subjects for 19 years and found no difference in all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Health behavior according to Bandura's self-efficacy hypothesis [12] can be promoted by social-cognitive means available ion OHI [13,14] and according to the Media Dependency Hypothesis, can be further amplified by the use of OHS [10,15] increasing the advantages of self-management practices in health [16] and significant effects that OHS or lack of, may have on CD patients [4,[17][18][19] have been reported especially among patients diagnosed with cancer, [20,21] heart condition, [22] diabetes [23] and other long-term conditions. [24,25] Use of OHS is indeed considered as significant means for self-management because it facilitates treatment and follow ups and prevents unnecessary health complications.…”
Section: Introductionmentioning
confidence: 99%
“…[5,35] On the positive side some studies point that use OHS increases the odds for monitoring a health problem in time due to delayed face-to-face appointments or timely access to the results of lab tests. [10,18,30,36,37] In a recent study among small samples of white females with diabetes, for example participants reported greater self-efficacy for managing their disease [23] the benefits of communicating with health care providers and/or website moderators to receive feedback and social support and tracking (e.g., graphical displays of uploaded personal data) were shown to particularly useful for self-management support but less so for improvements in medication adherence, biological outcomes and health care utilization. [38] On the negative side some studies suggest that use of OHS may fall behind the intended purposes and fail in providing effective health services.…”
Section: Introductionmentioning
confidence: 99%